Concept, features and types of civil legal relations - K. S. Naumenko (Bulletin of Kharkiv National University of Internal Affairs)
It has been established that civil legal relations are social relations between individuals and/or legal entities regulated by the rules of the civil branch of law and arising out of certain tangible and intangible benefits. Attention is drawn to the fact that civil legal relations are regulated not only by the rules of civil law, in particular, this is indicated by such a principle as freedom of contract in civil law. In other words, the content of civil law contracts may go beyond the legal relations provided for by the Civil Code of Ukraine.